Conference proceedings : Annual International Conference on Islamic Studies (AICIS) XII= Al Mu'tamar al sunuwiy al dawlliy al thaniy Asara li al dirasat al Islamiyyah, Surabaya, 5-8 November 2012 - Conference... (IAIN Sunan Ampel, 2012)
st,1/ws.c.1-3